Notas sobre a apropriação da escrita por crianças com Síndrome de Down - Oliveira, Anna Augusta Sampaio de [UNESP] (My University, 2010)
The project, developed at the Health and Education Studies ́ Center, in the Unity of the Science and Philosophy’s College, UNESP, Marilia ́s campus, had as goal the development of a study about the appropriation of writing by children with Down ’s syndrome. Five children, from 10 to 13 years old, on different situations of scholar levels, were took part in the project. As research procedure, it was developed weekly pedagogical interventions, based on Historical-Cultural Theory. At the beginning, the group presented different dimensions of approximation with the writing universe. It was observed advances on the graphic representation and on the individual trials of writing. Two children began to build small texts, one of the children is on the beginning of the alphabetic writing and two other children continue to present difficulties, getting close of the writing in a very not comfortable way, stuck on the scholar formality and a direct mediation to the words constitution is needed.

O projeto, desenvolvido no Centro de Estudos de Educação e Saúde, Unidade Auxiliar da Faculdade de Filosofia e Ciências, UNESP, campus de Marília – SP, teve como objetivo realizar um estudo sobre a apropriação da escrita por crianças com Síndrome de Down. Foram participantes do projeto 5 crianças, na faixa etária de 10 a 13 anos de idade, em diferentes situações de escolarização. Como procedimento de pesquisa, foram realizadas intervenções pedagógicas semanais, com base na Teoria Histórico-Cultural. Inicialmente, o grupo apresentava dimensões diferenciadas de aproximação com o universo escrito. Foram observados avanços nas representações gráficas e nas tentativas individuais de escrita. Dois alunos passaram a construir pequenos textos, um se encontra no início da escrita alfabética e dois continuaram a apresentar dificuldades, aproximando-se da escrita de forma muito tímida, presos à formalidade escolar e necessitando de uma mediação direta para a constituição das palavras.
Noticing about the writing appropriation in Down’s Syndrome children
Keywords: escrita; síndrome de Down; TEORIA HISTÓRICO-CULTURAL